Midwives' interventions for reducing fear of childbirth in pregnant women: a scoping review - Souto, Sandra Patrícia Arantes do (2022)
OBJECTIVE: The objective of this review was to map and analyze midwives' interventions for reducing fear of childbirth in pregnant women. INTRODUCTION: Fear of childbirth is a phenomenon negatively affecting women's health and well-being before and during pregnancy. Over the past few decades, there has been growing research interest in interventions for reducing fear of childbirth in pregnant women. One of the challenges in midwifery care is to provide an appropriate model of care for pregnant women with fear of childbirth. Further research efforts are needed to identify midwives' interventions for reducing fear of childbirth in pregnant women and to examine their characteristics. INCLUSION CRITERIA: This scoping review considered studies that included interventions for reducing fear of childbirth in pregnant women led and/or implemented by midwives during the antenatal period, and integrating all possible midwifery practice settings. Quantitative, qualitative, and mixed methods studies were included. This review also considered systematic reviews, text and opinion papers, and conference abstracts. METHODS: An a priori protocol was published and the JBI methodology for conducting scoping reviews was used. Published and unpublished literature in English, Portuguese, and Spanish from January 1981 to October 2020 were included. MEDLINE (PubMed), CINAHL Complete, APA PsycINFO, Scopus, Embase, Web of Science, SciELO, MedicLatina, Academic Search Complete, ERIC, Psychology and Behavioral Sciences Collection, and the Cochrane Library databases were searched. Searches for gray literature were also undertaken on the Repositório Científico de Acesso Aberto de Portugal, ProQuest Dissertations and Theses, British Library EThOS, OvidSP Resource Center, Banco de Teses da CAPES, and OpenGrey. A three-step search strategy was followed and the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews checklist was used. Two independent reviewers extracted the data using a data extraction tool developed specifically for this scoping review. RESULTS: A total of 3704 articles were identified and screened, of which 34 articles were included. The majority of studies had been published in the past 10 years (88.2%) in Scandinavian countries and Australia (79.4%). Several midwives' antenatal interventions were found, such as midwife-led team models of care. Midwives played a facilitator role that varied significantly across the included studies. In 20 studies (58.8%), midwives led and implemented the interventions alone (n  = 13; 38.2%) or with the participation of other health professionals (n  = 7; 20.6%). In the remaining 14 studies (41.2%), midwives were part of a multidisciplinary team that included different health professionals (mainly obstetricians and psychologists) who had been involved in delivering interventions alongside midwives or with minor participation from midwives. Counseling (n  = 12; 35.3%) and psychoeducation (n  = 8; 23.5%) were the most common midwife interventions for reducing fear of childbirth in pregnant women. CONCLUSIONS: Midwives working across their full scope of practice play a pivotal role in reducing fear of childbirth, which may help explain the variety of midwives' antenatal interventions. Reducing fear of childbirth in pregnant women and promoting normal childbirth as a positive experience are key features of midwives' interventions, which should include women's empowerment measures. Evidence-based midwife-led intervention programs for pregnant women with fear of childbirth should be designed and tested to improve clinical practice and women's reproductive outcomes and perinatal experiences.